Metafisika, Epistemologi, Metodologi, Logika, Etika, Estetika, dan Sejarah Filsafat - Suprianto, Hendra (Yayasan Sembilan Pemuda Indonesia, 2024)
This article is intended to describe the branches of philosophy and the history of philosophy and their scope, both descriptively and analytically. From the results of the review it can be seen that there are 6 branches of philosophy, namely metaphysics, epistemology, methodology, logic, ethics and aesthetics. Metaphysics is a branch of philosophy that discusses the problem of existence. Aristotle does not use the term metaphysics but uses the term protophilosophia. Epistemology comes from Greek, namely episteme means knowledge and logos means word, thought and knowledge. The methodologies commonly used are Bayani methodology and Burhani methodology. Logic cannot be separated from the process of finding out the values of truth and authenticity. Ethics is the main branch of philosophy that studies values or qualities which are the study of moral standards and judgments. Aesthetics is a science that discusses beauty, how it is formed, and how someone feels it.